DETECTION OF ANTIGENIC VARIATION OF CANINE PARVOVIRUS STRAINS OF INDIA USING DIFFERENTIAL PCR - Manoharan, Parthiban; SARANYA, R; DIVYA, KURUNCHI C; KUMANAN, K (The Indian Journal of Animal Sciences, 2011)
Canine parvovirus 2 (CPV2) is a highly contagious and fatal disease of dogs causing acute hemorrhagic enteritis and myocarditis.Â In this study, the faecal samples were initially screened using haemagglutination test followed by differential PCR assay using CPV2a and 2b antigenic type specific primers. Out of 53 samples screened, 17 samples were found to be positive by CPV2b specific primers. In PCR, the expected amplicon of 427 bp was observed in positive samples. The PCR products were sequenced and the phylogenetic analysis showed homology with CPV2b isolates. In addition to this, the presence of aminoacid aspartic acid at 426 positions clearly indicates the prevalence of CPV antigenic type 2b isolates in Tamil Nadu, India.